2023
DOI: 10.3390/plants12030628
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of the Sulfate Transporter Gene Family in Oilseed Crops: Camelina sativa and Brassica napus

Abstract: Sulfate transporters (SULTRs) are responsible for the uptake of sulfate (SO42−) ions in the rhizosphere by roots and their distribution to plant organs. In this study, SULTR family members in the genomes of two oilseed crops (Camelina sativa and Brassica napus) were identified and characterized based on their sequence structures, duplication events, phylogenetic relationships, phosphorylation sites, and expression levels. In total, 36 and 45 putative SULTR genes were recognized in the genomes of C. sativa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Also, the analysis of the structure of CsPLD and BnPLD genes discloses that the members of the alpha subfamily have fewer introns/exons. It has been reported that genes with fewer exons/introns are induced faster [49,54]. It seems that the smaller number of introns has an effect on the duration of the mRNA splicing process before leaving the nucleus, and as a result, they are translated earlier [47,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the analysis of the structure of CsPLD and BnPLD genes discloses that the members of the alpha subfamily have fewer introns/exons. It has been reported that genes with fewer exons/introns are induced faster [49,54]. It seems that the smaller number of introns has an effect on the duration of the mRNA splicing process before leaving the nucleus, and as a result, they are translated earlier [47,55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Ka/Ks value of all duplicated CsPLD and BnPLD pairs was estimated to be less than 1.0, revealing that the CsPLD and BnPLD family members survived under strong selection pressure of purification [46,47]. However, it was stated that purifying selection can generate pseudogenes and/or genes with conserved functions [48,49]. In addition, it seems that the expansion in CsPLDs happened much earlier than BnPLDs, and the evolution process of PLD was different in CsPLD and BnPLD family.…”
Section: Discussionmentioning
confidence: 99%
“…This increased activity in the sulfate transport pathway may serve to alleviate selenium stress, enhancing the plant's tolerance to selenium [42,43]. The findings provide a crucial theoretical basis for the treatment of selenium-rich products with exogenous selenium, offering insights into potential strategies to improve plant tolerance and mitigate the effects of selenium stress [44][45][46].…”
Section: Functional Diversity and Physicochemical Properties Of Jrsul...mentioning
confidence: 90%
“…In this present study, the Ka/Ks value of all duplicated VcCHS gene pairs was estimated to be ≤1.0, suggesting that the VcCHS family members survived the strong selection pressure of purification by elimination substitution and high selection pressure by natural selection during the evolutionary process [ 29 , 30 ]. Further, purifying selection can generate pseudogenes and/or genes with conserved functions [ 31 , 32 ]. Therefore, it can be inferred that the expansion of the CHS gene family contributed to the high flavonoid and anthocyanin characteristics of blueberry fruits.…”
Section: Discussionmentioning
confidence: 99%